Traditional folklore image of Moskal: social and psychological characteristics (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article investigates a traditional folk image of Moskal as a social and psychological type. Its interpretation is determined by various historical, political, psychological factors in terms of the history of Ukraine. As a rule, this image is represented in the folklore in two social and psychological ways. This Moscovite soldier (Russian soldier, sometimes Ukrainian by origin forced to serve foreign political interests) and Moskal, who is Russian by birth, but penetrating in the Ukrainian society after the well known events. There are certain differences in folk’s assessments of these two types.Thus, the attitude to the first type is connected and mostly influenced by national understanding of human dependence on unfair circumstances and considering historical background. This refers to the phenomenon of compulsory recruitment and military service, which was performed after Zaporizhian Sich destruction. Moscovite soldier of the first type, according to the folk understanding is an unhappy faithless, doomed to constant hardships person. Often Moscovite (former countryman) is perceived as immoral man, that is why it is better to handle carefully with such people. The second type (Moskal, who is Russian by birth) is usually interpreted by folk consciousness in the categories “another”, “alien”. This Moskal is an enemy against whom Cossacks are constantly fighting (mean, treacherous and cunning). This Moskal is a commander of the royal army or a Moscovite soldier, who stays at a peasant family. Usually they are negatively labeled in the folk consciousness.This paper emphasizes that the interpretation of the Moskal image in folklore is not the evidence of Ukrainian national intolerance but the result of deep person’s behavior analyzing, his acting as a representative of a particular social stratum, which is caused by social and psychological factors. Our people have always been open to a dialogue, creative collaboration and sharing traditions. However, Ukrainians rightly demand respect in return to their culture, abhor violence, arrogance, deception, trimmering. These national concepts should be looked as the sources of national treating to Moskal soldier and vividly represented in folklore.
Keywords: folklore; Moscovite soldier; moral and ethical principles